Disaster planning and control - Kramer, William M. (William Michael) (PennWell/Fire Engineering, 2009)
In this new book, Bill Kramer examines the complexities of disaster planning and control, covering the concepts of disaster management, development of disaster and emergency operation plans, and much more. Through examples and case studies, the book is designed to allow the fire officer to study how the fire service has been involved with responding to various disasters and, by learning from the past and understanding the concepts presented, make a difference in the overall outcome of future events.